Triptycene-based porous photoluminescent polymers with dual role: efficient capture of carbon dioxide and sensitive detection of picric acid. (March 2022) - Ansari, M.; Das, N.
Abstract: Design and synthesis of unique photoluminescent triptycene-based porous polymers (TBP-OH and TBP-NH 2 ) bearing active functional groups is described herein. Pd catalyzed Sonogashira cross-coupling reaction was utilized to obtain these polymeric networks that are nanoporous and strongly fluorescent in THF. In solid state, these polymers demonstrated CO2 uptake up to 92 mg g −1 at 273 K/1bar and H2 up to 16 mg g −1 at 77 K/1bar which may be attributed to the presence of 3D robust triptycene and CO2 -philic groups –OH and –NH2 in their polymeric framework. TBP-OH and TBP-NH 2 also selectively capture CO2 over nitrogen and methane. CO2 capture by TBP-OH and TBP-NH 2 is a physisorption process and hence reversible in nature. Suspensions of TBP-OH and TBP-NH 2 in THF are strongly fluorescent and are also capable of detecting picric acid (an environmental pollutant and explosive) in trace amounts. The Stern–Volmer quenching constants (Ksv ) for detection of picric acid (PA) are in the order of 10 5 M −1 . Graphical abstract: Image 1 Highlights: One-pot and facial synthesis of triptycene-based nanoporous and photoluminescent polymers (TBP-NH 2 and TBP-OH ). Polymers contain ample number of dangling CO2 -philic groups (–OH and –NH2 ): a pre-requisite for a CO2 adsorbent. Polymers capture CO2 reversibly up to 9.2 wt % at 273 K and 1 bar. Polymers displayed good CO2 /N2 selectivity up to 29.3 at 273 K and 1 bar pressure: These porous polymers are efficient chemosensors for picric acid (PA) (a hazardous and powerful explosive nitroaromatics).